2017
DOI: 10.3389/fphar.2017.00373
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Anti-tumoral Effects of the Flavonoid Apigenin in Malignant Mesothelioma

Abstract: Malignant mesothelioma (MM) is a tumor arising from mesothelium. MM patients’ survival is poor. The polyphenol 4′,5,7,-trihydroxyflavone Apigenin (API) is a “multifunctional drug”. Several studies have demonstrated API anti-tumoral effects. However, little is known on the in vitro and in vivo anti-tumoral effects of API in MM. Thus, we analyzed the in vitro effects of API on cell proliferation, cell cycle regulation, pro-survival signaling pathways, apoptosis, and autophagy of human and mouse MM cells. We eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 79 publications
0
43
0
Order By: Relevance
“…Apigenin also blocks the degradation of IκBα in lung cancers, which further blocks the separation of IκBα from the NF-κB heterodimer [ 26 ]. And in malignant mesothelioma, apigenin treatment showed anti-cancer effects in vitro and in vivo by inhibiting NF-κB nuclear translocation and AKT activation and modulating MAPK signaling pathways [ 91 ].…”
Section: Signaling Transduction Modulation By Apigenin In Cancer Thermentioning
confidence: 99%
“…Apigenin also blocks the degradation of IκBα in lung cancers, which further blocks the separation of IκBα from the NF-κB heterodimer [ 26 ]. And in malignant mesothelioma, apigenin treatment showed anti-cancer effects in vitro and in vivo by inhibiting NF-κB nuclear translocation and AKT activation and modulating MAPK signaling pathways [ 91 ].…”
Section: Signaling Transduction Modulation By Apigenin In Cancer Thermentioning
confidence: 99%
“…The Consulting the literature showed that the phenolic acid components chlorogenic acid (Xue et al, 2017;Shao, Zhang, Chen, & Sun, 2015) and caffeic acid (Brautigan, Gielata, Heo, Kubicka, & Wilkins, 2018), and the flavonoids scutellarin (Nie et al, 2018;Sun et al, 2018;Tang & Gao, 2019), isoorientin (Huang, Jin et al, 2018;Lin et al, 2016), isovitexin (Lv, 2018), scutellarein (Jiang et al, 2018;Lu, Li, Li, & Asia, 2017;Zheng et al, 2017), luteolin (Niu, Guo, Gan, Bao, & Ren, 2015) and apigenin (Bhattacharya et al, 2018;Masuelli et al, 2017;Cai et al, 2011) had different degrees of inhibition on tumor cells. Among them, caffeic acid, isoorientin, isovitexin, luteolin and apigenin had better antiliver tumor activities.…”
Section: Analysis Of Migration Components In Plasmamentioning
confidence: 99%
“…Masuelli et al [211] demonstrated that apigenin in MM cells caused apoptosis and not autophagy by altering Bax/Bcl2 ratio. Apigenin also caused the activation of p53 and caspase-9.…”
Section: Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%